Assessing quality of life and readmission rates among women in psychiatric care: a mixed-method study - Celso Gonçalves Alves; Blanca Elena Guerrero Daboin; Jussara de Azevedo Pereira; Esthefany Pereira Estevam; Italla Maria Pinheiro Bezerra; Carlos Eduardo Siqueira; Tassiane Cristina Morais (BMC Psychology)
Abstract Background The mental health of women is significantly shaped by gender-related issues stemming from social and cultural disparities, which intensify female susceptibility and culminate in mental disorders. Despite a plethora of studies delineating the effects of gender on mental health, there exists a conspicuous deficiency in research investigating women’s viewpoints regarding their own experiences of rehospitalization. Therefore, the principal aim of our investigation was to assess the relationship between rehospitalization and the Quality of Life (QoL) among women undergoing treatment at a psychiatric care institution. Methods We employed a mixed-methods research framework to examine the QoL and the variables pertinent to the readmission of twenty women from a public psychiatric hospital situated in the interior region of Espírito Santo, Brazil. The quantitative aspect evaluated QoL using the scores and analytical guidelines established by the World Health Organization Quality of Life Brief Version (WHOQOL-BREF) questionnaire. The results from this phase were subjected to descriptive statistical analysis. The qualitative data were derived from semi-structured interviews aimed at exploring the factors associated with readmission; the insights obtained underwent narrative analysis. This study was approved by the ethics committee. The interviews were only carried out after the patients were medically discharged. Results Women who are readmitted do not have their problems viewed objectively and, consequently, are not having them resolved, as the factors contributing to the mental health of these patients are complex and span across the domains of physical, psychological, social relationships, and environment. There is a notably low overall QoL (M = 47.78) in the study population, with particularly poor scores in the environment (44.49), psychological (47.71) and social relationships (48.54) domains. These findings align with participants’ testimonies, which emphasize the role of unstable living conditions, financial insecurity, social isolation, and family dysfunction in their ongoing struggles with mental health. Conclusions The mental health outcomes of women are shaped by a multitude of factors, encompassing social support, access to resources, and individual coping strategies. Approaches to mental health care that are humanized and that address these factors are imperative for enhancing QoL and mitigating readmission rates.